Optimization of WEDM Development Para-Meter for HDS H13 BY Using Taguchi Orthogonal Array: Novel Approach - M, Monika; Kumar, Amit (International Journal of Computer Sciences and Engineering, 2020)
Wire electrical discharge machining is extensively used in machining of conductive materials. The WEDM process has the ability to machine complex shapes and hard electrically conductive metal components precisely. The main goal of wire electrical discharge machine manufacturers and users are to achieve a better stability and high productivity of the process with desired accuracy and minimum surface damage. The main objectives of the present research are to experimentally study the effect of various process parameters like pulse on time, pulse off time, wire feed, and wire tension on the performance measures like material removal rate, surface roughness and wire wear ratio. WEDM is a widely recognized unconventional material cutting process used to manufacture components with complex shapes and profiles of hard materials. In this paper we are presenting the development of WEDEM process using various pre define parameters using Taguchi method.